2021
DOI: 10.1038/s42255-021-00356-0
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-induced FOXO4 blunts human CD4+ T helper cell responsiveness

Abstract: Intermittent fasting blunts inflammation in asthma 1 and rheumatoid arthritis 2 , suggesting that fasting may be exploited as an immune-modulatory intervention. However, mechanisms underpinning anti-inflammatory effects of fasting remain poorly characterized 3 , 4 , 5 . Here, we show that fasting in humans is sufficient to blunt CD4 + T helper cell respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 37 publications
3
55
0
1
Order By: Relevance
“…In this study, the 24-h fast was shown to have more robust gene regulatory responses versus refeeding when compared to the overnight fast, supporting the concept that the hormetic stress of the longer fast initiates more robust immunomodulatory effects. The unbiased bioinformatic analysis of the data in the PBMCs supported the results that fasting had a robust effect on CD4 + T cells, although the study could not distinguish between cell intrinsic regulatory effects versus paracrine effects on the cells from the 24-h fast [ 32 ]. Prior studies showed that serum extracted from fasting versus refed subjects and used for the incubation of THP-1 macrophages showed differential modulation of the NLRP3 inflammasome [ 6 , 12 ], although what factors in serum orchestrated this immunomodulation has not been determined.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In this study, the 24-h fast was shown to have more robust gene regulatory responses versus refeeding when compared to the overnight fast, supporting the concept that the hormetic stress of the longer fast initiates more robust immunomodulatory effects. The unbiased bioinformatic analysis of the data in the PBMCs supported the results that fasting had a robust effect on CD4 + T cells, although the study could not distinguish between cell intrinsic regulatory effects versus paracrine effects on the cells from the 24-h fast [ 32 ]. Prior studies showed that serum extracted from fasting versus refed subjects and used for the incubation of THP-1 macrophages showed differential modulation of the NLRP3 inflammasome [ 6 , 12 ], although what factors in serum orchestrated this immunomodulation has not been determined.…”
Section: Resultsmentioning
confidence: 87%
“…In the initial study on this cohort of subjects comparing RNAseq analysis and flow cytometry, it was found that the immunomodulatory effects of the 24-h fast were more robust than the overnight fast when both groups were compared to refeeding [ 32 ]. Hence, an additional integrated bioinformatics approach was employed to evaluate if we could uncover additional differences in circulating protein levels that could correlate with PBMC gene expression level changes in response to 24 h of fasting or refeeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations